2019
DOI: 10.1108/ijchm-10-2018-0816
|View full text |Cite
|
Sign up to set email alerts
|

When do customers engage in brand pages? Effects of social presence

Abstract: Purpose Drawing upon the social presence theory, this paper aims to propose three social presence variables in the brand page context (the brand page as a medium, the presence of other customers and interaction with the brand page manager) and to test their effects on customer engagement behavior (CEB) and customer-brand identification (CBI). Design/methodology/approach A total of 340 responses were collected via an online research platform and analyzed using structural equation modeling analysis. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 58 publications
1
24
1
Order By: Relevance
“…Third, social presence was combined with the present ELM, indicating that different levels of social presence would influence perceived trust and participation toward brand microblogs based on both central and peripheral routes. Although previous studies have found that social presence can be antecedents of users' perception or behaviors toward social media (Lu et al, 2016;Song and Moon, 2019), this study provides evidence showing the moderating effect of social presence in an extended ELM model. The effect of trust toward brand microblog on consumer participation will differ according to the level of social presence.…”
Section: Theoretical Implicationscontrasting
confidence: 73%
“…Third, social presence was combined with the present ELM, indicating that different levels of social presence would influence perceived trust and participation toward brand microblogs based on both central and peripheral routes. Although previous studies have found that social presence can be antecedents of users' perception or behaviors toward social media (Lu et al, 2016;Song and Moon, 2019), this study provides evidence showing the moderating effect of social presence in an extended ELM model. The effect of trust toward brand microblog on consumer participation will differ according to the level of social presence.…”
Section: Theoretical Implicationscontrasting
confidence: 73%
“…In the context of e-commerce, social presence has been investigated as an important element that can affect online consumers' loyalty, (Cyr et al, 2007), attitude (Hassanein and Head, 2007), trust (Ogonowski et al, 2014;Ye et al, 2019), experience and satisfaction (McLean and Osei-Frimpong, 2017;Song et al, 2019), as well as online purchase intentions .…”
Section: Travel Service Computer-mediated Interactionsmentioning
confidence: 99%
“…Similarly, social presence theory has been introduced to discuss the logic behind social interaction and interpersonal relationships (Short et al, 1976), which later on became popular in the communication and information system domains (e.g. Lu et al, 2016;Schrum et al, 2012), but is being discussed in the CE context (Busalim et al, 2021;Hayes et al, 2020;Song et al, 2019). Psychological ownership theory has been originally offered to further the discourse on ownership toward organizations (Pierce et al, 2001), but the theory is gaining momentum in the domain of digital marketing (Morewedge et al, 2020), and specifically CE (Li et al, 2021).…”
Section: Research Questions Authorsmentioning
confidence: 99%